The Truama of the "Boat People" - Refuge Editor (Refuge: Canada’s Journal on Refugees, 1983)
Sixty-four Vietnamese Chinese refugees were asked to report "What happened during the flight?" as part of a survey conducted by Lawrence Lam of York University. The chart lists the events most frequently experienced by these "boat people."